Utilization of the Kutuh Village Tourism Website in Optimizing E-Tourism Based Tourism Village Promotion - Putera, Wayan Andrika; Rahardian, Rifky Lana; Pradipta, I Made; Sukawidana, I Wayan (Information Technology and Science (ITScience), 2025)
Kutuh Village is one of the villages in the south of Bali Island. Kutuh Village has tourism potential for international and domestic visitors. To increase the number of visitors to Kutuh Village, more support is needed to promote tourism in Kutuh Village. One thing that can be developed is E-Tourism. This service can be provided via a website, easily accessed anywhere and anytime using digital tools. Therefore, it is necessary to design an e-tourism application as a web-based tourism promotion in the Kutuh Tourism Village. So that it can attract more visitors in line with the objectives of this research. This web-based application has 2 users, namely visitors and admin. Visitors can view information about tourist attractions and events on this application in Indonesian and English. Apart from that, visitors can provide rates and comments in the application. This application system uses PHP as a programming language. Using waterfall as a system development method, in collecting data using observation methods, literature studies and similar literature. The system design uses DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), conceptual database, table structure and then implemented. The positive feedback from the 11 respondents from Kutuh Village, who rated the application with an average score of 90.59%, suggests a high level of acceptance and satisfaction among local users. With the existence of e-tourism, the Kutuh Tourism Village is expected to increase tourist visits